2014
DOI: 10.1007/s11033-013-2927-2
|View full text |Cite
|
Sign up to set email alerts
|

Chlamydia trachomatis infection and human papillomavirus in women with cervical neoplasia in Pernambuco-Brazil

Abstract: Chlamydia trachomatis (CT) is the most common bacterial cause of sexually transmitted disease. High-risk human papillomavirus (HR-HPV) is considered the main etiological agent for cervical neoplasia. Evidences showed that the presence of co-infection of CT and HR-HPV plays a central role in the etiology of cervical intraepithelial neoplasia (CIN) and cervical cancer. The goals of this study were: evaluate the human papillomavirus (HPV) and CT prevalence among Brazilian women with abnormal cytology and provide … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
26
0
3

Year Published

2014
2014
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(33 citation statements)
references
References 59 publications
3
26
0
3
Order By: Relevance
“…A large body of epidemiological data suggests that C. trachomatis may play a role as a co-factor in cervical carcinogenesis (Silins et al, 2005), although the question of how C. trachomatis interacts with HPV in the transformation process is still a matter of debate (Idahl et al, 2010;Paavonen, 2012;Silva et al, 2014;Tavares et al, 2014). Tavares et al (2014) suggested that C. trachomatis infection could influence the natural history of HPV, proposing that C. trachomatis and HPV might mutually interact with each other, rather than sharing a common way of transmission.…”
Section: Discussionmentioning
confidence: 99%
“…A large body of epidemiological data suggests that C. trachomatis may play a role as a co-factor in cervical carcinogenesis (Silins et al, 2005), although the question of how C. trachomatis interacts with HPV in the transformation process is still a matter of debate (Idahl et al, 2010;Paavonen, 2012;Silva et al, 2014;Tavares et al, 2014). Tavares et al (2014) suggested that C. trachomatis infection could influence the natural history of HPV, proposing that C. trachomatis and HPV might mutually interact with each other, rather than sharing a common way of transmission.…”
Section: Discussionmentioning
confidence: 99%
“…A baixa prevalência do HPV 18 encontrada nesta população foi semelhante aos resultados encontrados pela Internacional Agency for Research on Cancer -IARC (2007) em um estudo de meta-análise e por Bruno et al (2014) no rastreamento de 351 mulheres do Estado da Bahia. Estas variações na prevalência dos tipos de HPV podem ser elucidadas pela complexa interação entre os tipos de HPV com fatores imunogenéticos do hospedeiro, idade, localização geográfica ou ainda pela escolha da sequência de primers utilizados na PCR e genotipagem (Freitas et al, 2007;Tavares et al, 2014). Além disso, analisouse coinfecção entre os tipos virais, com destaque para infecção simultânea entre os quatro tipos em estudo, com percentual de 7,2%, o que pode sugerir um fator predisponente desta população ao desenvolvimento de lesões, isto por que o presente estudo demonstrou ocorrência de coinfecções próximas aos resultados encontrados em estudos com mulheres sintomáticas, que variaram entre 10% e 18,18%, sendo estes os valores mais altos para os tipos 16 e 18 (Boch et al, 2002;Trottier e Franco, 2006 A presente pesquisa demonstrou tanto analogias quando discrepâncias em relação aos estudos supracitados, podendo estes resultados conflitantes serem elucidados pela variabilidade de hábitos e costumes de cada região.…”
Section: Discussionunclassified
“…Apenas nos estados da Bahia (31,0%) 18 e de Pernambuco (23,8%) 16 foram registradas prevalências maiores, porém com tamanho amostral inferior ao utilizado neste estudo.…”
Section: Discussionunclassified
“…No Brasil, a prevalência de infecções por C. trachomatis varia entre 4,3% e 31,0%, conforme estudos de base populacional/comunitária de grandes centros urbanos e estudos de base clínica, realizados com participantes frequentadoras de ambulatórios e clínicas ginecológicas 10,11,12,13,14,15,16,17,18,19 . Nas comunidades amazônicas, há escassez de conhecimento sobre a epidemiologia da infecção endocervical por C. trachomatis, o que impossibilita a criação de diretrizes que estabeleçam o rastreio e controle dessa infecção.…”
Section: Introductionunclassified